Fashion storytelling: translating Bornean landscapes into contemporary fashion aesthetics - Saliang, Prinses; Razali, Adlina; Mat Mazelan, Muhamad Zharin Hariz; Saaidin, Husna; Wan Kamarul Baharin, Wan Nadhra Ixora (College of Creative Arts, 2025)
This study investigates how natural and cultural landscapes can be translated into contemporary fashion aesthetics, using Bohey Dulang, Sabah, as a case study. While Malaysian fashion has historically privileged Peninsular motifs such as batik and kebaya, the ecological and cultural richness of East Malaysia remains underrepresented. Addressing this gap, the research explores how Bohey Dulang’s volcanic topography, marine biodiversity, and Bajau Laut mythology can inform fashion design as a medium of cultural storytelling and identity expression. Adopting a qualitative, design-led methodology, the study integrates visual archiving, surface embellishment experimentation, and the Interpretative Engagement Framework (Drew & Guillemin, 2014). Ecological and cultural references were translated into fashion components including fabric manipulations, kaleidoscopic digital prints, and silhouette constructions. The findings demonstrate that landscapes and myths can be semiotically reinterpreted into wearable forms, creating narratives that embody both environmental awareness and intangible cultural heritage. The study contributes to fashion scholarship by advancing the discourse on place-based design, cultural sustainability, and fashion storytelling. It proposes a framework for understanding fashion as an interpretative bridge that connects ecological landscapes and cultural memory to contemporary design practice. Furthermore, the research underscores fashion’s potential as a vehicle for cultural preservation and ecological advocacy within Southeast Asia’s broader design context.